2017
DOI: 10.1111/1471-0528.15015
|View full text |Cite
|
Sign up to set email alerts
|

Respectful care during childbirth in health facilities globally: a qualitative evidence synthesis

Abstract: BackgroundWhat constitutes respectful maternity care (RMC) operationally in research and programme implementation is often variable.ObjectivesTo develop a conceptualisation of RMC.Search strategyKey databases, including PubMed, CINAHL, EMBASE, Global Health Library, grey literature, and reference lists of relevant studies.Selection criteriaPrimary qualitative studies focusing on care occurring during labour, childbirth, and/or immediately postpartum in health facilities, without any restrictions on locations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
289
2
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(326 citation statements)
references
References 77 publications
14
289
2
21
Order By: Relevance
“…The findings from this qualitative synthesis have some similarities with other qualitative and mixed‐methods reviews on quality of maternity care and companionship (Beake 2018; Bohren 2015a; Kabakian‐Khasholian 2017; Munabi‐Babigumira 2017; Shakibazadeh 2018); however none of these reviews had the same focus as this synthesis.…”
Section: Discussionmentioning
confidence: 67%
“…The findings from this qualitative synthesis have some similarities with other qualitative and mixed‐methods reviews on quality of maternity care and companionship (Beake 2018; Bohren 2015a; Kabakian‐Khasholian 2017; Munabi‐Babigumira 2017; Shakibazadeh 2018); however none of these reviews had the same focus as this synthesis.…”
Section: Discussionmentioning
confidence: 67%
“…2 We would like to thank the authors for the interest shown in our paper and for raising this important issue. Here we will try to highlight the views of women interviewed in the primary studies included in our qualitative evidence synthesis (QES) on the issue.…”
mentioning
confidence: 89%
“…Here we will try to highlight the views of women interviewed in the primary studies included in our qualitative evidence synthesis (QES) on the issue. 2 In recent years, perspectives on maternity care have gradually shifted from a model of medical paternalism towards one of autonomy and shared decision-making. Similar to other studies, our QES showed that pregnant women are active in seeking information and request opportunities to participate in healthcare decisions, 2,3 especially in high-income countries.…”
mentioning
confidence: 99%
See 2 more Smart Citations